CRISE FISCAL DOS ESTADOS E O CASO DO RIO DE JANEIRO / STATE FISCAL CRISES, AND THE CASE OF RIO DE JANEIRO - Guilherme Mercês; Nayara Freire (Geo UERJ, 2017)
doi: 10.12957/geouerj.2017.32070 This article analyzes public accounts of Brazilian states, focusing on Rio de Janeiro. We examined the public debt and the key indicators for public account dynamics: staff costs, accounts payable, and investments. The first conclusion is that few states have a debt problem. The second conclusion is that the fiscal crisis is structural, notwithstanding the fall in revenues due to the economic recession. It is related to the high budget staff cost fixed share, especially due to social security imbalance. Thus, moments of fall in revenues result in high deficits. In addition to that, budget rigidity has resulted in great liquidity problems, which are expressed by the excessive use of accounts payable without equivalent cash flow hedge. Consequently, we also concluded that commitment to the fiscal recovery program proposed by the Federal Government seems inevitable to the states of Rio de Janeiro, Rio Grande do Sul and Minas Gerais. The agreement requirements, however, are not enough to prevent new renegotiation of state debts in a few years.